Quantification of greenhouse gas emissions in the Figuil-Cameroon cement plant between 2016–2020 using the Genetic Algorithm-Gaussian coupling - Nkongo Essombo Samuel Maximin; Edouma Fils Prosper; Ekani Roger Yannick; Njomo Donatien; Essombo Essombo Bathelemy; Fotsing Talla Cyrille; Koumi Ngoh Simon; Nsouandele Jean Luc (Discover Applied Sciences)
Abstract The environmental impact of the cement industry is particularly significant in the release of suspended particulates and also substances such as nitrogen oxides and sulphur dioxide. This industry has very high energy requirements that can only be met by fossil fuels, hence its significant contribution to greenhouse gas (GHG) emissions. In Cameroon, for example, people living in the vicinity of cement works suffer from lung diseases (pneumonia, bronchitis, asthma and tuberculosis) due to atmospheric pollution from emissions from these industries. This study therefore assesses the quantities of GHGs emitted by the Figuil cement plant in northern Cameroon between 2016 and 2020, their distribution and mitigation in the atmosphere, and defines an environmental safety perimeter around the plant. The genetic algorithm-Gaussian (GA-Gaussian) coupling method was used for this assessment. The results obtained indicate that the Figuil cement plant emits an average of 526 kg of carbon dioxide (CO2), 971.41 kg of methane (CH4) and 309.41 kg of nitrous oxide (N2O) per month. GHGs gradually diminish with distance from their point of emission. The results show that GHGs no longer have a direct effect after 400 m from the cement plant, which represents the atmospheric safety zone around this cement production plant. Article Highlights’ Greenhouse gas emissions; Trends and variations in greenhouse gas emissions; Dispersion of atmospheric pollutants